2023
DOI: 10.1021/acs.molpharmaceut.3c00872
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Translatability of In Vitro and In Vivo Models to Evaluate Caprate as a Permeation Enhancer

Prosper Emeh,
Katarina Breitholtz,
Staffan Berg
et al.

Abstract: Transient permeation enhancers (PEs) have been widely used to improve the oral absorption of macromolecules. During pharmaceutical development, the correct selection of the macromolecule, PE, and the combination needs to be made to maximize oral bioavailability and ensure successful clinical development. Various in vitro and in vivo methods have been investigated to optimize this selection. In vitro methods are generally preferred by the pharmaceutical industry to reduce the use of animals according to the "re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Kasendra et al reported the basal P app of Cascade Blue-Dextran 3 kDa in a duodenal organoid Chip model as ∼1 × 10 –6 cm/s . Comparatively, the P app for FD4 in Caco-2 Transwells is typically reported as <8 × 10 –8 cm/s. ,, Here, we reported a basal P app of FD3 in Transwells as 5.3 ± 0.8 × 10 –8 cm/s in line with previous reports and P app of FD4 in Chips 3.2 ± 1.8 × 10 –7 cm/s. Tan and colleagues compared a Caco-2 Transwell and Chip model and reported an FD4 P app of ∼2.5 × 10 –7 cm/s (Chip) and <1 × 10 –7 cm/s (Transwell) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Kasendra et al reported the basal P app of Cascade Blue-Dextran 3 kDa in a duodenal organoid Chip model as ∼1 × 10 –6 cm/s . Comparatively, the P app for FD4 in Caco-2 Transwells is typically reported as <8 × 10 –8 cm/s. ,, Here, we reported a basal P app of FD3 in Transwells as 5.3 ± 0.8 × 10 –8 cm/s in line with previous reports and P app of FD4 in Chips 3.2 ± 1.8 × 10 –7 cm/s. Tan and colleagues compared a Caco-2 Transwell and Chip model and reported an FD4 P app of ∼2.5 × 10 –7 cm/s (Chip) and <1 × 10 –7 cm/s (Transwell) .…”
Section: Discussionsupporting
confidence: 91%
“…Adding NaCap increased the P app by 7-fold and 2-fold in Transwells and Chips, while sucrose monolaurate increased the P app by 140-fold and 8-fold, respectively. The increase in permeability in the presence of PEs in the Chip model trends more appropriately with observations in ex vivo and in vivo models. , …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation